Diatonic Illusions and Chromatic Waterwheels: Edward Elgar’s Concept of Tonality - Chandler, Oliver (Journal of the Society for Musicology in Ireland, 2020)
In a 1915 article for the Westminster Gazette, Edward Elgar described chromatic major-third cycles as waterwheels, which are adjuncts to a house. If this metaphor is read tonally, then the ‘house’ in question might be thought of as a tonic. Chromaticism – the ‘waterwheel’ – serves to power this tonic, in much the same way that actual waterwheels power mechanical processes in the buildings to which they are affixed. Contrary to modern neo-Riemannian theories, then, which stress the origin of chromatic progressions in ‘non-tonal’ syntaxes, I argue that Elgar experienced tertiary chromaticism as being tonally grounded. The ‘Romance’ from Elgar’s Violin Sonata, Op. 82, might be taken as a practical elucidation of this waterwheel theory if the same qualities ascribed by Elgar to foreground chromatic-third cycles are projected onto background structures too (i.e. progressions which present surface harmonic content in massive rhythmic augmentation). However, the Romance’s structural chromaticism only becomes apparent when it is demonstrated that the movement’s background is sometimes dissimulated by diatonic foreground illusions. The ‘house’ Elgar’s ‘waterwheel’ powers, then, cannot be assumed to be a particular diatonic collection. In this case, it is a single chord, which can be set off as a tonal centre in a number of ways, both diatonic and chromatic.